A fibrinogen-mimicking, activated-platelet-sensitive nanocoacervate enhances thrombus targeting and penetration of tissue plasminogen activator for effective thrombolytic therapy. - Huang,Y; Jiang,J; Ren,J; Guo,Y; Zhao,Q; Zhou,J; Li,Y; Chen,R (Advanced Healthcare Materials, 2022)
Development of a fibrinolytic system with long circulation time, high thrombus targeting, efficient thrombus penetration, effective thrombolysis and minimal hemorrhagic risk remains a major challenge. Herein, inspired by fibrinogen binding to activated platelets in thrombosis, we report a fibrinogen-mimicking, activated-platelet-sensitive nanocoacervate to enhance thrombus penetration of tissue plasminogen activator (tPA) for targeted thrombolytic therapy. This biomimetic nanothrombolytic system, denoted as RGD-Chi@tPA, was constructed by "one-pot" coacervation through electrostatic interactions between positively charged arginine-glycine-aspartic acid (RGD)-grafted chitosan (RGD-Chi) and negatively charged tPA. Flow cytometry and confocal laser scanning microscopy measurements showed a targeting of RGD-Chi@tPA to activated platelets. Controlled tPA release triggered by activated platelets at a thrombus site was demonstrated. Its targeted fibrinolytic and thrombolytic activities were measured in vitro models. The pharmacokinetic profiles showed that RGD-Chi@tPA could significantly prolong circulation time compared to free tPA. In a mouse tail thrombus model, RGD-Chi@tPA displayed efficient thrombus targeting and penetration, enabling a complete vascular recanalization as confirmed by the fluorescence imaging, histochemical assay and laser speckle contrast imager. Consequently, RGD-Chi@tPA induced a substantial enhancement in thrombolysis with minimal hemorrhagic risk compared to free tPA. This simple, effective and safe platform holds a great promise for development of thrombolytic nanomedicines. This article is protected by copyright. All rights reserved.